Hubungan Pengetahuan Ibu Terhadap Pemberian ASI Eksklusif Di Wilayah Kerja Puskesmas Batunyala - Nining Fatria Ningsih; Eli Arsanah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The purpose of this study was to determine the relationship between maternal knowledge about exclusive breastfeeding and the provision of exclusive breastfeeding in Puskesmas Batunyala, Lajut Village in 2024. Method: this research is the type of analytical correlation research with cross-sectional approach, data collection using a questionnaire with a total sampling technique, and data analysis using the Chi-Square test. Result: from 48 respondents, the results showed that most breastfeeding mothers were aged 20-35 years, 41 (85.42%), had a high school education, 24 (50%), were housewives, 45 (93.75%), were multiparous, 38 (79.17%), had a good level of knowledge, 31 (64.58%), most of them gave exclusive breastfeeding, namely 34 (70.83%), the Chi-Square Test obtained a p-value of 0.043 <0.05 indicating that there is a statistically significant relationship between maternal knowledge and exclusive breastfeeding.